Voluntary scuba diving as a method for monitoring invasive exotic marine species - Mangelli, Tarcio S.; Zapelini, Cleverson; da Rocha, Wesley Duarte; Schiavetti, Alexandre (Ethnobiology and Conservation, 2020)
Monitoring surveys provide data needed to assess ecosystem conditions in places where bioinvasion occurs. The collection of data by volunteer researchers (citizen science) is an alternative for scientists and research agencies that lack information but do not have sufficient financial resources. The objective of this study was to evaluate marine monitoring using voluntary recreational scuba diving to identify invasive exotic marine species at eight diving sites distributed between the north of Ilha Grande and the municipality of Angra dos Reis in the Central Channel of Ilha Grande Bay, Rio de Janeiro state. During the three months of study, 207 questionnaires were evaluated. The results showed that the group of volunteer divers with more experience identified a greater number of invasive exotic species compared to the group of divers with less experience. No statistical difference was found in the number of species identified between the groups of volunteer divers with and without a species identification chart. As a recommendation for the use of citizen science, it is necessary to use divers with greater diving experience. Developing stricter protocols for the identification of invasive exotic marine species is essential for the collection of quality data. The improvement of monitoring programs based on citizen science can provide useful information for research on biodiversity in marine environments, significantly reducing financial costs and time in the field, in addition to contributing to the ecological knowledge, awareness and environmental education of participants